Individual differences in cognitive control over emotional material modulate cognitive biases linked to depressive symptoms. Issue 4 (19th May 2017) - Everaert, Jonas; Grahek, Ivan; Koster, Ernst H.W.
ABSTRACT: Deficient cognitive control over emotional material and cognitive biases are important mechanisms underlying depression, but the interplay between these emotionally distorted cognitive processes in relation to depressive symptoms is not well understood. This study investigated the relations among deficient cognitive control of emotional information (i.e. inhibition, shifting, and updating difficulties), cognitive biases (i.e. negative attention and interpretation biases), and depressive symptoms. Theory-driven indirect effect models were constructed, hypothesising that deficient cognitive control over emotional material predicts depressive symptoms through negative attention and interpretation biases. Bootstrapping analyses demonstrated that deficient inhibitory control over negative material was related to negative attention bias which in turn predicted a congruent bias in interpretation and subsequently depressive symptoms. Both shifting and updating impairments in response to negative material had an indirect effect on depression severity through negative interpretation bias. No evidence was found for direct effects of deficient cognitive control over emotional material on depressive symptoms. These findings may help to formulate an integrated understanding of the cognitive foundations of depressive symptoms.